Analisis Kesulitan Menulis Teks Eksplanasi Siswa Kelas V UPTD SD Negeri 3 Jangka - Devi Wulandari; Alfi Syahrin; Muhammad Darwis; Zainal Arifin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the low ability of elementary school students in writing explanatory texts. The purpose of this study is to identify the types of difficulties in writing explanatory texts, analyze the factors that cause them, and describe the teachers' efforts in overcoming these difficulties. The study used a qualitative approach with a case study type. The subjects were 29 fifth-grade students of UPTD SD Negeri 3 Jangka. Data were collected through writing tests, analysis of student writing documents, and learning observations. Data were analyzed descriptively qualitatively based on aspects of content, organization, and writing mechanics. The results showed that students experienced difficulties in the aspects of content, organization, and mechanics. Difficulties in the content aspect were indicated by the still low ability to develop main ideas into detailed descriptions. In the organizational aspect, students were not yet able to compose cohesive and coherent paragraphs. Meanwhile, in the mechanical aspect, errors in the use of capital letters and punctuation were still found. Factors causing difficulties consisted of internal factors, namely low interest in writing, limited vocabulary, and weak visual memory, as well as external factors in the form of the use of conventional learning methods, lack of literacy support at home, and excessive use of gadgets. Efforts made by teachers include utilizing visual media such as Smart TVs, implementing multisensory strategies, and providing structured writing exercises.